Strain effects on the valence band structure, optical transitions, and light gain spectrums in zinc-blende GaN quantum wells - Lokot, L.O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
A study for the effects of size quantization and strain effects on the valence band spectra, the interband matrix elements, and the light gain spectrum in zinc-blende GaN quantum wells is presented. In the framework of the effective mass theory, the Schrödinger equation is solved for the valence bands with a 3×3 block Hamiltonian. The results are illustrated for the GaN/Al₀.₁₉Ga₀.₈₁N quantum well. It is shown, that the biaxial strain causes quite significant changes to the gain spectra in spatially confined structures. It is shown, that laser effect is suppressed with arising of the circular loop of valence band maxima in the heterostructure under the tensile strain, while under the compressive strain, the stimulated emission is pronounced. Our results show the internal strain effects are important in optical properties of GaN and associated quantum well structures.